The Growth, Yield and Quality of Elephant Grass (Pennisetum purpureum) Spesific Toleran of Acid Soils by Mutagenesis with Ethylmethane Sulfonate - Munasik, Munasik; Sutrisno, CI; Anwar, S; Prayitno, CH (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2012)
The purpose of this research was to know the effect of ethylmethane sulfonate (EMS) on the growth, yield and quality of Elephant grass. The experimental method with completely randomized design (CRD) was applied. Fifeteens plot area 2 x 3 m2 were used in this experiment. There were three treatments and five replications. The treatments consisted of R0 = Elephant grass control, R1 = Elephant grass with 0.1% EMS treatment, and R2 = Elephant grass with 0.2% EMS treatment. The variables were the development (height of plant, the number of leaf, the leaf area and ratio of stem to leaf), yield (forage/plant, forage/plot and dry matter yield and quality (dry matter, crude protein and crude fiber content) of Elephant grass. These results of variance analysis showed that the treatments significantly affected on the height of plant, the forage yield/plant and the crude protein content but not significantly affected on the number of leaf, the leaf area, ratio of stem to leaf, forage yield/plot, dry matter yield, dry matter and crude fiber content.Key words : ethylmethane sulfonate, Pennisetum purpureum, growth, yield, quality Animal Production 14(2):87-91